Peran Kepala Sekolah Dalam Peningkatan Mutu Pendidikan Islam - SAYUTI, FAUZI (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2016)
The school principal has a very important role in improving the quality of the institution. This is because; in the hands of a leader who is a 'master' in his institution will occur changes to the quality standards expected. The exact roles and appropriate functions must be done by a school principal to achieve the goal. A school principal is emphasized to understand what role should be done, whether as an educator, manager, administrator, supervisor, leader, innovator, or motivator. By understanding and doing the school principal well so the school principal will be able to lead the institution well.In addition, the school principal must have spirit of struggle as agent of change in improving the quality of education to the defined quality standard. This can be done with the steps include: the formulation of the vision, mission, goals and objectives of institution, decision-making, SWOT analysis, programs plan to improve the quality, transparency, participation of school and society, independence and accountability, and changes to the quality standard.